PERSEPSI GURU TERHADAP PENDEKATAN DEEP LEARNING PADA PEMBELAJARAN IPAS DI PEKANBARU - Diva Nadia, Ria; Guslinda; Erlisnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the fact that some elementary school teachers in Pekanbaru still do not fully understand the deep learning approach in IPAS learning, particularly in connecting learning concepts with critical, reflective, and contextual thinking skills. This study aimed to describe teachers’ perceptions of the deep learning approach in IPAS learning in Pekanbaru. The research employed a descriptive quantitative method with a survey approach. The population consisted of 192 public elementary school teachers from eight districts in Pekanbaru City, with a sample of 100 teachers selected using a purposive sampling technique. Data were collected through a Likert-scale questionnaire developed based on three main aspects of the deep learning approach, namely meaningful learning, mindful learning, and joyful learning. The data were analyzed using descriptive statistics in the form of percentages. The results showed that the majority of teachers had positive perceptions toward the deep learning approach in IPAS learning. Teachers believed that this approach could help students understand concepts more deeply, relate learning materials to daily life, improve critical thinking awareness, and create an enjoyable learning atmosphere. In addition, the instrument testing results indicated that all questionnaire items were valid with a significance value of < 0.05 and reliable with a Cronbach’s Alpha value of 0.766. Therefore, the deep learning approach is considered relevant in supporting more meaningful and effective IPAS learning in elementary schools.